1995
DOI: 10.1074/jbc.270.38.22314
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular L-Glutamate Transporter in Microvesicles from Bovine Pineal Glands

Abstract: Pinealocytes, endocrine cells that synthesize and secrete melatonin, possess a large number of synaptic-like microvesicles (MVs) containing the L-glutamate transporter (Moriyama, Y., and Yamamoto, A. (1995) FEBS Lett., 367, 233-236). In this study, the L-glutamate transporter in MVs isolated from bovine pineal glands was characterized as to its driving force, requirement of anions, and substrate specificity. Upon the addition of ATP, the MVs accumulated L-glutamate. The uptake was significantly dependent on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 41 publications
1
45
0
2
Order By: Relevance
“…The addition of either L-aspartate or D-aspartate at 1.0 mM during the assay had a little effect on the ATP-dependent glutamate uptake, indicating that the glutamate transporter does not recognize L-aspartate or D-aspartate as a substrate, one of the characteristics of vesicular glutamate transporters (25)(26)(27). The inability of DNPI to transport D-aspartate was also confirmed by the direct uptake assay (Fig.…”
Section: Fig 2 Expression and Localization Of Dnpi In Pinealocytesmentioning
confidence: 61%
See 2 more Smart Citations
“…The addition of either L-aspartate or D-aspartate at 1.0 mM during the assay had a little effect on the ATP-dependent glutamate uptake, indicating that the glutamate transporter does not recognize L-aspartate or D-aspartate as a substrate, one of the characteristics of vesicular glutamate transporters (25)(26)(27). The inability of DNPI to transport D-aspartate was also confirmed by the direct uptake assay (Fig.…”
Section: Fig 2 Expression and Localization Of Dnpi In Pinealocytesmentioning
confidence: 61%
“…In the earlier stage of studies, vesicular glutamate transporter was defined as the ATP-dependent proton conductor-sensitive glutamate transport activity in synaptic vesicles, but little was known about the protein nature of the transporter at the molecular level (25)(26)(27)39). In the last year, two groups have independently reported that BNPI is vesicular glutamate transporter itself and that BNPI is a potential tool for substantial studies on vesicular glutamate transporter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7). The involvement of the brain-specific Na ϩ -dependent inorganic phosphate transporter (BNPI), recently identified as a vesicular glutamate transporter in neuronal cells (23,35), in the accumulation of D-aspartate is unlikely because a vesicular glutamate transporter does not recognize D-aspartate as a substrate (36,37) and is not expressed in PC12 cells (35). The absence of BNPI in PC12 cells was confirmed by immunoblotting using the sitespecific polyclonal antibodies against BNPI (data not shown).…”
Section: Methodsmentioning
confidence: 78%
“…The V1 domain, containing the ATP catalytic site, is composed of a hexamer of three subunit A (65-77 kDa) and three subunit B (55-60 kDa) proteins plus accessory subunit C (40-45 kDa), D (33-34 kDa) and E (26)(27)(28)(29)(30)(31)(32)(33). The VO domain, as a proton transporter, is composed of four subunits of 16 kDa, one subunit of 20 kDa and one subunit of 115 kDa.…”
mentioning
confidence: 99%